A Journey to the World of the Smallest Animals: Arthropods as an Educational Resource in Early Childhood Education Teacher Training - Gálvez Esteban, Rosa; Meleto-Alcíbar, Rosario (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
In this study we present a set of preliminary results obtained through a survey from an educational project based on arthropods as an educational resource in the initial training of Early Childhood Educators. The objective is twofold, first to make students realise of the teaching possibilities that arthropods offer, second, to change their frequently hostile or indifferent attitude towards this animal group. Most of the students showed a positive reaction against arthropod´s activities. Yet some difficulties were identified in their learning process related to the right use of the dichotomous key and the binocular loupe.